Injectable Dual‐Dynamic‐Bond Cross‐Linked Hydrogel for Highly Efficient Infected Diabetic Wound Healing. Issue 14 (18th May 2022) - Yao, Shasha; Zhao, Yueqi; Xu, Yifei; Jin, Biao; Wang, Monian; Yu, Congcong; Guo, Zhengxi; Jiang, Shengnan; Tang, Ruikang; Fang, Xiangqian; Fan, Shunwu
Abstract: Diabetic wound is a significant challenge for clinical treatment with high morbidity and mortality. Plenty of hydrogels with good biocompatibility have been widely used in diabetic wound healing. However, most of them cannot be directly absorbed and utilized by the wounds, which prolongs the regeneration time. Here a new type of healing hydrogel is developed that is based on histidine, a natural dietary essential amino acid that is significant for tissue formation. The amino acid is cross‐linked with zinc ions (Zn 2+ ) and sodium alginate (SA) via dynamic coordinate and hydrogen bonds, respectively, forming a histidine‐SA‐Zn 2+ (HSZH) hydrogel with good injectable, adhesive, biocompatible, and antibacterial properties. Application of this dual‐dynamic‐bond cross‐linked HSZH hydrogel accelerates the migration and angiogenesis of skin‐related cells in vitro. Furthermore, it significantly promotes the healing of infected diabetic wounds in vivo and uniquely allows a full repair of wounds within ≈13 days, while ≈27 days are required for the healing process of the control group. This work provides a new strategy for designing wound dressing materials, that weakly cross‐linked material based on tissue‐friendly micromolecules can heal the wounds more efficiently than highly cross‐linked materials based on long‐chain polymers. Abstract : A dual‐dynamic‐bond cross‐linked hydrogel is synthesized using tissue‐friendly micromolecules for infected diabetic wound treatment. The hydrogel dissolves rapidly in wounds and releases chemicals that can be completely absorbed and directly utilized for tissue regeneration. In vivo experiments indicate that the healing rate of the dual‐dynamic‐bond cross‐linked histidine‐SA‐Zn 2+ (HSZH) hydrogel is more than 100% higher than that of the control group.